Khả năng chấp nhận công nghệ Blockchain của khách hàng trong các dịch vụ ngân hàng tại Việt Nam - Nguyễn Hữu, Huân; Đào Thái, Minh; Lê Thái, Hòa; Huỳnh, Thiện; Huỳnh Thạch, Trúc; Phạm Cao Mỹ, Tâm (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Blockchain technology has been attracting investment from many countries, including Vietnam due to its potential to change many economic fields, typically the financial - banking sector. However, the level of acceptance of this technology in the banking sector has not been much tested in Vietnam. Therefore, it is difficult to estimate whether these services will be accepted by customers when it is put out for public use. The purpose of the article is to estimate the adoption rate of banking services using Blockchain technology. The article is built in the direction of quantitative research based on the technology acceptance model (TAM), combined with Google Forms to collect research data and using SmartPLS 4 software to analyze information data through the SEM structural model. The results of our research show that two strong factors, Social influence and Experience, have positive impacts on Customer trust in banking services based on Blockchain technology. Trust is a key factor driving the adoption of blockchain banking services.
Keywords: Blockchain; Banking Services; The TAM Model